The effect of strength vs. power training on throwing performance - Zaras, N.; Spengos, K.; Methenitis, S.; Papadopoulos, C.; Karampatsos, G.; Georgiadis, G.; Stasinaki, A.; Manta, P.; Terzis, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Shot put is a power demanding activity (Zatsiorsky et al., 1981). Recently it was shown that strength training enhances muscle mass and shot put performance, in novice throwers (Terzis et al., 2008) but the effect of power training on shot put performance remains unexplored. Aim of this study was to investigate the effects of 6 weeks strength vs. power training on shot put performance. Methods: Seventeen participants were divided into Strength (N = 9) or Power (N = 8) groups. Training was performed 3/week for 6 weeks with 3 resistance exercises: leg press, bench press and semi-squat. For the Strength group, the load was set at 6RM while the Power group trained with ballistic exercises with 30% of 1RM (Kyröläinen et al., 2005). The following tests were performed before and after the training period: shot put throws, counter movement jumps (CMJ), Wingate, 1RM strength and ballistic throws tests. Vastus lateralis thickness, pennation angles and fascicle lengths were examined with ultrasonography, while fiber type composition and cross sectional area (fCSA) measured on histochemically stained muscle samples. Results: Shot put performance increased significantly but similarly after strength and power training (7-13.5% vs. 6-11.5%, respectively). Leg press 1RM increased more after strength than after power training. Power training induced an increase in CMJ by 8.5% (p=0.006), and in ballistic throws by 9-26% (p<0.05), while strength training did not alter performance in these tests. Peak power during the Wingate test increased similarly in both groups. Muscle thickness increased only after strength training (10%, p=0.004). Muscle fCSA increased in all fiber types after strength training by 17-25% (p<0.05), while only type IIx fibers hypertrophied significantly after power training. Type IIx fibers (%) decreased after strength but not after power training. Discussion: The results of the present study suggest that shot put throwing performance can be increased similarly after 6 weeks of strength or power training, in novice throwers. Improvements in shot put performance after strength training could be attributed mainly to muscle hypertrophy while improvements after power training might be attributed to adaptations in type IIx muscle fibers, although neural adaptations might have contributed also. It appears that ballistic power training might be used effectively during the last weeks before competition, when the strength training load is usually reduced, in order to increase muscle power and shot put performance in novice throwers.